2002
DOI: 10.1542/peds.109.4.594
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sleep Aids During the First Year of Life

Abstract: Objective.-In an attempt to foster self-soothing during the night, a novel sleep aid infused with maternal odor was introduced to 4 groups of infants ranging in age from 3 to 12 months. Infants' use of parent-provided sleep aids also was examined.Methodology.-Nighttime sleep and waking behaviors were videotaped for 2 consecutive nights on 3 occasions over a 3-month interval. Using all-night video recording, the study examined the infant's use of a novel sleep aid and parent-provided sleep aids during sleep ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
1

Year Published

2005
2005
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
12
1
1
Order By: Relevance
“…In a short-term longitudinal study from 3 to 12 months of age, Burnham et al (2002a) reported that infant sleep location in a separate room was associated with self-soothing at all time points. Self-soothing was also related to greater delay in parental intervention for night crying.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a short-term longitudinal study from 3 to 12 months of age, Burnham et al (2002a) reported that infant sleep location in a separate room was associated with self-soothing at all time points. Self-soothing was also related to greater delay in parental intervention for night crying.…”
Section: Discussionmentioning
confidence: 99%
“…genetic, maturational) and environmental factors are important in sleep development in infants, toddlers and preschoolers (Fagioli, Ficca, & Salzarulo, 2002;Fehlings, Weiss, & Stephens, 2001;Sadeh & Anders, 1993). Some of the factors that have been associated with the timing of this developmental milestone, characterized by a decline in nighttime awakenings, include bedtime parent-child interactions (Anders, Halpern, & Hua, 1992;Lozoff, Wolf, & Davis, 1984), sleep habits (Crowell, Keener, Ginsburg, & Anders, 1987;Lozoff et al, 1984); individual differences in child temperament (Hayes, Parker, Sallinen, & Davare, 2001;Keener, Zeanah, & Anders, 1988;Scher, Tirosh, & Lavie, 1998), sleep-wake rhythm (Burnham, Goodlin-Jones, Gaylor, & Anders, 2002a;Sadeh, Lavie, Scher, Tirosh, & Epstein, 1991), maternal psychological state (Morell, 1999;Scher & Blumberg, 1999), use of sleep aids/security or transitional objects (Burnham et al, 2002a;Winnicott, 1953), and aspects of the sleep environment and sleeping arrangement style (McKenna, Mosko, Dungy, & McAninch, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These sleep aids, commonly objects such as pacifiers, blankets, toys, stuffed animals, or children's thumbs for sucking, are depicted as facilitating children's falling asleep by providing a sense of comfort and security. 66 The use of a sleep aid is intimately linked to bedtime behavior, sleeping arrangements, and individuation-separation processes during the transition from wakefulness to sleep and, thus, to cultural beliefs and standards. Notably, Morelli et al 63 reported that no transitional objects were used by the Mayan infants in their study, a pattern that seems to typify cosleeping cultures.…”
Section: Sleep Aidsmentioning
confidence: 99%
“…In another study, a moderate to high degree of concordance was found between parental reports of infants' use of particular objects as sleep aids and observer coding of sleep aid use during a total of six all-night videotape sessions. Where discordance was evident, the error was on the side of the parents underreporting the use of sleep aids (Burnham et al 2002). Studies examining correspondence between parent report measures of temperament and observer ratings have reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%